The Implementation of Wordwall Media to Improve Students’ Learning Outcomes in Islamic Religious Education (PAI) for Fifth-Grade Students at SDN Lambada Klieng, Aceh Besar - Syamsidar, Syamsidar; Marzuki, Marzuki; Nurbayani, Nurbayani; Harmaini, Harmaini (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This classroom action research aimed to improve students’ learning outcomes and engagement in Islamic Religious Education (PAI) through the integration of Wordwall-based digital media and the Two Stay Two Stray (TSTS) cooperative learning model. Conducted at SD Negeri Lambada Klieng, Aceh Besar, during the 2024/2025 academic year, the study involved 25 fifth-grade students and followed the Kemmis and McTaggart (1998) spiral model consisting of two cycles with stages of planning, action, observation, and reflection. Data were collected through observation, tests, and documentation, then analyzed using descriptive quantitative and qualitative methods. The findings showed a significant improvement in students’ performance and participation, as indicated by the increase in average scores from 68.4 in Cycle I to 91.2 in Cycle II and in classical mastery from 44% to 96.7%. Students also displayed greater motivation, collaboration, and confidence in expressing ideas. The integration of Wordwall and TSTS created an engaging, interactive, and reflective learning atmosphere that enhanced both cognitive achievement and affective development. This study concludes that combining Wordwall with TSTS effectively supports meaningful and student-centered learning in Islamic Religious Education, aligning with social constructivist principles, and is recommended as an innovative pedagogical strategy to enhance learning effectiveness in elementary schools.